(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Aerodynamics plays a crucial role while designing any automobile components. Due to the aerodynamics the entire performance of the automotive will be changed. With an improvement in computer technology, manufacturers are looking toward computational fluid dynamics instead of wind tunnel testing to reduce the testing time and cost. In this paper a car model considered and it is modeled using solid works modeling software. The car material is stainless steel. The lift and drag of production vehicle are determined by the analysis of flow of air around it using Ansys. The aerodynamic analysis of the design parameter of car will be performed by using a suitable turbulence model and to compare the drag coefficient of design of car model by using CFD software result and experimentally result and the results will be validated by CFD analysis/experimental studies. The result of software analysis has agreed excellently with field experimentally results. The aerodynamic and crash analysis on car with of material Al 6061&AISI 4130 with wall and vehicle is considered The given model is tested under frontal collision conditions and the resultant deformation and stresses are determined with respect to a time of 80 Mille sec for ramp loading using ANSYS software. The crash analysis simulation and results can be used to assess both the crashworthiness of current frame and to investigate ways to improve the design. This type of simulation is an integral part of the designcycle and can reduce the need for costly destructive testing program.